Aberrant Resting-State Functional Brain Connectivity of Insular Subregions in Obstructive Sleep Apnea - Kong, Linghong; Li, Haijun; Shu, Yongqiang; Liu, Xiang; Li, Panmei; Li, Kunyao; Xie, Wei; Zeng, Yaping; Peng, Dechang (Frontiers in Neuroscience, 2022)
The insular cortex is a cortical regulatory area involved in dyspnea, cognition, emotion, and sensorimotor function. Previous studies reported that obstructive sleep apnea (OSA) shows insular tissue damage and abnormal functional connections for the whole insula. The insula can be divided into different subregions with distinct functional profiles, including the ventral anterior insula (vAI) participating in affective processing, dorsal anterior insula (dAI) involved in cognitive processing, and posterior insula (PI) involved in the processing of sensorimotor information. However, the functional connectivity (FC) of these insular subregions in OSA has yet to be established. Hence, the purpose of this study was to explore the resting-state FC of the insular subregions with other brain areas and its relationship with clinical symptoms of OSA. Resting-state functional magnetic resonance imaging data from 83 male OSA patients and 84 healthy controls were analyzed by whole-brain voxel-based FC using spherical seeds from six insular subregions, namely, the bilateral vAI, dAI and PI, to identify abnormalities in the insular subregions network and related brain regions. Ultimately, the Pearson correlation analysis was carried out between the dysfunction results and the neuropsychological tests. Compared with the healthy control group, the OSA patients exhibited disturbed FC from the dAI to areas relevant to cognition, such as the bilateral cerebellum posterior lobe, superior frontal gyrus, right middle frontal gyrus and middle temporal gyrus; decreased FC from the vAI to areas linked with emotion, such as the bilateral fusiform gyrus, superior parietal lobule, precuneus and cerebellum posterior lobe; and abnormal FC from the PI to the brain regions involved in sensorimotor such as the bilateral precentral gyrus, right superior/middle temporal gyrus and left superior frontal gyrus. The linear regression result showed that the apnea-hypopnea index was positively correlated with the increased FC between the right PI and the right precuneus (after Bonferroni correlation, P < 0.001) In conclusion, the abnormal FC between insular subregions and other brain regions were related to cognitive, emotional and sensorimotor networks in OSA patients. These results may provide a new imaging perspective for further understanding of OSA-related cognitive and affective disorders.